If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(q-3)+6=3(q+10)-q
We move all terms to the left:
4(q-3)+6-(3(q+10)-q)=0
We multiply parentheses
4q-(3(q+10)-q)-12+6=0
We calculate terms in parentheses: -(3(q+10)-q), so:We add all the numbers together, and all the variables
3(q+10)-q
We add all the numbers together, and all the variables
-1q+3(q+10)
We multiply parentheses
-1q+3q+30
We add all the numbers together, and all the variables
2q+30
Back to the equation:
-(2q+30)
4q-(2q+30)-6=0
We get rid of parentheses
4q-2q-30-6=0
We add all the numbers together, and all the variables
2q-36=0
We move all terms containing q to the left, all other terms to the right
2q=36
q=36/2
q=18
| 9+z=13 | | 0=-0.2t^2+5t-17 | | 10k+1=40+7k | | C(t)=110+25t | | 8/7c+8=-8 | | (13,7)m=2 | | 66=4(5n+3)-6n | | -2b-b=6 | | 4+2x-2=8x+4-5x | | t+t-1=160 | | -5-3(-6+3r)=7-3r | | 12y+10y=100 | | 418=-22d | | 3x+10=6x+14 | | C(t)=310 | | 22=-6-7n | | 12(6-y)=9 | | 0=4+n.20 | | T=1,200+0.08s | | 1/2n-3=4n+11 | | 29=-7x+4(x+8) | | (3x-12)=x | | z+2=-14 | | 13m+8+8m=3(7m-2) | | 5(13)=d | | 4/7m-1/2=2/3 | | 18=-7x+x | | k+76.7=47.2 | | (x-1)(2x^2-3x+1)=0 | | 6x-14=x | | 12a+3=-16 | | 10=32+2c |